Comparison of cycle threshold values of the Cobas HPV test and viral loads of the BMRT HPV test in cervical cancer screening - Yang, Qing; Du, Hui; Qu, Xinfeng; Dai, Wenkui; Gui, Liming; Li, Changzhong; Wang, Chun; Guo, Chunlei; Zhang, Yi; Wei, Lihui; Belinson, J. L.; Wu, Ruifang (Frontiers in Public Health, 2022)
Objective: To validate the HPV viral loads reflected by cycle threshold values of Cobas4800 as the viral load indicators by verifying the consistency of it with the viral loads per unit (10,000 cells) from BMRT assay. Methods: 4485 cases selected by nested case-control randomization from the Chinese Multi-Center Screening Trial (CHIMUST). 4290 with HPV testing results and relevant Ct values from Cobas4800 available, we tested the entire sample set with the BMRT HPV testing assay and analyzed their agreement with Cobas4800 followed by a comparison of the CtV from Cobas4800 and viral load (lg) from BMRT by lesion grade. Results: 4290/4485 women (mean age 45.4 years) who had complete data were included in the analysis. The consistency of genotypes from Cobas and BMRT for hrHPV, HPV-16, HPV-18, and 12-HPV pool was 94.9% (4070/4290, Kappa=0.827), 99.1% (4251/4290, Kappa=0.842), 99.6% (4273/4290, Kappa=0.777), and 95.3% (4089/4290, Kappa=0.821), respectively. Further analysis shows that any inconsistency between the two assays is likely among samples with comparatively lower viral loads. When analyzing per lesions of CIN2+ and CIN3+, the CtV from Cobas and VL (lg) from BMRT are highly correlated inversely and follow the linear regression for HPV16 and 12-HPV pool (Pearson’s or Spearman’s correlation coefficient (r): In CIN3+, rHPV16 =-0.641, 12-HPV pool HPV 16 12-HPVP<0.001;r=-0.343,P=0.109;InCIN2+,r=-0.754,P<0.001;r 12-HPV pool =-0.429,P<0.001). Conclusion: The CtV from Cobas4800 and the viral load (lg) of per unit cells from the BMRT are well correlated for physician-collected samples. Cobas CtV is worthy of further study for clinical application.